An octad of fumarate hydratase-deficient uterine leiomyomas: Case series with review of literature from a single institution - Nishtha Batra; Bharat Rekhi; Santosh Menon; Neha Mittal; Kedar K. Deodhar (Indian Journal of Pathology and Microbiology)
Background: Fumarate hydratase (FH)-deficient (FH-d) leiomyomas are included in the recent World Health Organization fascicle of the female genital tumors. These are known to be associated with hereditary leiomyomatosis and renal cell cancer (HLRCC) syndrome. The tumors can be diagnosed based on certain histopathological features, along with loss of immunohistochemical expression of FH immunostain in most tumors. Currently, there is no documentation on these tumors from our subcontinent. Aims: We analyzed eight FH-d leiomyomas diagnosed at our institute. Results: The most common presentation was vaginal bleeding (menorrhagia). Pelvic ultrasonogram revealed multiple fibroids in most patients except in two, who harbored a single fibroid. The size of these fibroids ranged from 3 to 19 cm. Five patients underwent myomectomies, while three underwent a total abdominal hysterectomy and bilateral salphino-ophorectomy. The most consistently observed histopathological features were hemangiopericytomatous vascular patterns, cytoplasmic globules, increased cellularity, distinct eosinophilic nucleoli, and cytological atypia (8/8, 100% tumors), followed by multinucleate giant cells and perivascular edema, seen in 62% and 50% tumors, respectively. Immunohistochemically, all tumors were positive for desmin, smooth muscle actin, and h-caldesmon and showed loss of FH immunostain, along with low Ki-67/MIB1. None of those patients had any renal or cutaneous manifestations. Conclusions: This constitutes the first such study from the Indian subcontinent and reinforces that although uterine leiomyomas constitute an integral component of the diagnosis of HLRCC syndrome, these occur in the absence of renal or cutaneous manifestations. FH-d uterine leiomyomas are more likely sporadic and could be a false alarm to raise the possibility of HLRCC with their exclusive presence.